Strategy of Internationalization for the Higher Education System (on the Example of Georgia) - Eka Chokheli; Onise Alpenidze (ISJ Theoretical & Applied Science, 2015)
The article considers the significance, motifs and prospects of the higher education internationalization, as that of the subsequent process of globalization. The strategy of internationalization of the higher educational institutions is assessed in Georgia, the country having been an active member of the international environment for some 20 years now. In addition, the trends promoting the integration of the enlightening system and its establishment in the global environment were also identified.
Keywords: 330; Internationalization; Strategy; Higher Education; Mobility; Globalization; Strategy; University education; Mobility